Does an effective government lower COVID19's health impact? Evidence from Viet Nam - Dang Duc Anh; Ngoc Anh Tran (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2022)
Government effectiveness has played an important role in tackling the crisis caused by the coronavirus (COVID-19) pandemic. This paper discusses the different aspects of government effectiveness in explaining the variation in the COVID-19 confirmed cases and death levels in Viet Nam. We use the Provincial Governance and Public Administration Performance Index in 2019 to measure the quality of government effectiveness at the local level. The findings show the importance of health system capacity in the battle against COVID-19. We find that increased government transparency is significantly associated with lower confirmed rates. For the impact of the level of participation, we find that provinces that have higher quality of village head elections or where people have more opportunities to participate tend to have lower infected cases, especially where people participate in the formal and informal association and have voted in the National Assembly election.
Keywords: I15; I18; H12; O57; 330; COVID-19; pandemic; government effectiveness; Viet Nam